Language, culture, and image-driven interpretations in translation: A case for the university translation classroom in Ukraine - Vakhovska, Olha; Isaienko, Olha (Amazonia Investiga, 2021)
In this paper, we develop a theory of image-driven interpretations for the translation studies domain. Interpretations make the core of translation and are explained in terms of mental images. An image-driven interpretation gives a meaning to a source-language word and finds in the target language the word to capture this meaning, which is a creative act and a cross-cultural transfer. An interpretation is ‘drawing’ images in the human mind by the powers of the mind’s representational content. Our theory proposes a role for etymological insight in boosting translation students’ interpretive skills via exposed inner word forms. These archaic archetypal images contain culture-specific information transmitted through human generations with the help of language. Inner word forms are non-trivial triggers in cultural exposure that raise students’ awareness of the native and foreign cultures and add an in-depth dimension to regular vocabulary work and other good practices in the translation classroom. We pin down some of the influences that native Ukrainian words and borrowings have had on the Ukrainians’ interpretive mind.